Comparative proteogenomic analysis of right-sided colon cancer, left-sided colon cancer and rectal cancer reveals distinct mutational profiles - Imperial, Robin; Ahmed, Zaheer; Toor, Omer M.; Erdogan, Cihat; Khaliq, Ateeq; Case, Paul; Case, James; Kennedy, Kevin; Cummings, Lee S.; Melton, Niklas; Raza, Shahzad; Diri, Banu; et al. (BMC, 2018)
Right-sided colon cancer (RCC) has worse prognosis compared to left-sided colon cancer (LCC) and rectal cancer. The reason for this difference in outcomes is not well understood. We performed comparative somatic and proteomic analyses of RCC, LCC and rectal cancers to understand the unique molecular features of each tumor sub-types. Utilizing a novel in silico clonal evolution algorithm, we identified common tumor-initiating events involving APC, KRAS and TP53 genes in RCC, LCC and rectal cancers. However, the individual role-played by each event, their order in tumor development and selection of downstream somatic alterations were distinct in all three anatomical locations. Some similarities were noted between LCC and rectal cancer. Hotspot mutation analysis identified a nonsense mutation, APC R1450* specific to RCC. In addition, we discovered new significantly mutated genes at each tumor location, Further in silico proteomic analysis, developed by our group, found distinct central or hub proteins with unique interactomes among each location. Our study revealed significant differences between RCC, LCC and rectal cancers not only at somatic but also at proteomic level that may have therapeutic relevance in these highly complex and heterogeneous tumors.
Keywords: Right-sided colon cancer; Left-sided colon cancer; Rectal cancers; Clonal evolution; Proteomics; Hotspot mutations; Biochemistry & Molecular Biology; Oncology